(untitled) (Conferencea, 2023)
"Toothache" is a word that scares children and adults, men and women. One of the main causes of severe pain in the teeth is caries. This disease can be dangerous in different degrees, but it must be treated in any case. In the article, we will talk about the most effective methods of caries treatment, as well as the prevention of the disease.